Economic Aspects and Factors of Educational and Labor Migration of Kazakhstan Youth Abroad - A. K. Jussibaliyeva; D. M. Iskakova; B. B. Duisenbayeva; S. S. Tleuberdiyeva; D. B. Iskakova (Экономика: стратегия и практика)
The outflow of young people from the country for education and employment abroad is one of the most acute socio-economic problems for Kazakhstan. Taking into account the international competition in education and the imperfection of the labor market in the country, stopping the emigration of young people in the near future seems to be a difficult task.   The purpose of the study is to identify and substantiate the economic aspects and factors of educational and labor migration of Kazakh youth abroad. Today, young people of Kazakhstan travel to almost all regions and countries of the world. Youth migration has both positive and negative aspects. There were developed 3 types of online questionnaires for particular categories of respondents: 1) graduates of secondary education (27 questions), 2) graduates of bachelor’s degree (27 questions), 3) young people working and living abroad (23 questions). SPSS Software was used for data analysis. The positive consequences include raising the level of qualifications and knowledge of young people, exploring new opportunities for self-realization. However, an urgent problem is a fact that the educational and labor migration of young people turns into permanent or non-return migration. The analysis allowed us to identify the dominant factors of «attraction-pushing», which have been studied and are considered as determining the migration movement of young people abroad. The combination of attracting and pushing factors influencing the migration decisions of young people can be very complex and diverse, however, in most cases, the main factors are economic, social, and demographic factors of migration.